Peserta Didik dalam Perspektif Islam dan Barat: Sebuah Tinjauan Filosofis - Hariyanto, Wawan; Syafiq, Muhammad Azryan (Ta lim Jurnal Pendidikan Agama Islam dan Manajemen Pendidikan Islam, 2024)
Education has an important role in shaping the character and potential of learners, which is influenced by the philosophical views underlying each education system. In the Islamic perspective, learners are seen as beings with a pure fitrah and the potential to develop holistically, including spiritual, intellectual, and physical aspects. In contrast, in Western educational philosophy, especially since the Enlightenment era, learners are defined as autonomous and rational individuals, with an emphasis on freedom of thought and critical exploration. This research aims to conduct a philosophical analysis of the concept of learners in Islamic and Western perspectives, and explore the implications of these philosophical differences for the goals and methods of education. This research uses a qualitative approach with a literature study method, which involves a review of primary and secondary sources related to Islamic and Western educational views. The results show that despite fundamental differences in the orientation of education, both perspectives have the same goal, which is the optimal development of human potential. The conclusion of this study is that the synergy between the two approaches can offer a more holistic approach to education that is relevant to the challenges of the contemporary world.